2015
DOI: 10.1111/1755-6724.12568
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Geochemical Characteristics of Hydrogen in Natural Gas from the Jiyang Depression, Eastern China

Abstract: Hydrogen gas accelerates hydrocarbon generation, but little is known about its distribution and origin in petroliferous basins, which has hindered the further exploration. Taken the Jiyang Depression in eastern China as an example, this study collected natural gas from different tectonic units, and analyzed various geochemical characters including gas contents, and carbon and hydrogen isotopic composition. The result shows that: (1) hydrogen gas is widespread distributed, but its content is very low, which typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Mango et al ( , 1997 showed in an open system that the reaction of exogenous hydrogen with organic matter promotes the rate of HC generation under the action of transition metals. Meng et al (2015) confirmed that deep hydrogenrich fluids can activate and increase the HC regeneration of ancient source rocks through experiments. Liu et al (2016) showed that there is Fischer-Tropsch-type (FTT) interaction between H 2 and CO 2 produced by the thermal alteration of source rocks in the geological environment to synthesize HCs.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Mango et al ( , 1997 showed in an open system that the reaction of exogenous hydrogen with organic matter promotes the rate of HC generation under the action of transition metals. Meng et al (2015) confirmed that deep hydrogenrich fluids can activate and increase the HC regeneration of ancient source rocks through experiments. Liu et al (2016) showed that there is Fischer-Tropsch-type (FTT) interaction between H 2 and CO 2 produced by the thermal alteration of source rocks in the geological environment to synthesize HCs.…”
Section: Introductionsupporting
confidence: 53%
“…A large amount of gas components carried by the deep-derived fluids contain volatile materials, such as H 2 , CH 4 , H 2 S, CO 2 , N 2 , and He. As one of the main volatile fluids, the distribution of geologic H 2 (molecular hydrogen) is widespread in ocean ridges, active tectonic belts, and the Precambrian or Cenozoic strata distributed on land (Jeffrey and Kaplan, 1998;Allen and Seyfried, 2004;Newell et al, 2007;Tivey, 2007;Bradley and Summons, 2010;Sherwood-Lollar et al, 2014;Meng et al, 2015;Etiope, 2017;Guélard et al, 2017;Etiope and Whiticar, 2019;Bougault et al, 2019;Klein et al, 2019;Klein et al, 2020). H 2 has a variety of genetic types, including the release of deep magma degassing, the serpentinization of ultrabasic-basic rocks (Sherwood-Lollar et al, 2014;Etiope, 2017;Klein et al, 2019;Klein et al, 2020), radiolysis of water due to the presence of radioactive minerals (Sherwood-Lollar et al, 2014;Milesi et al, 2016), mechanical cracking of Si-bearing rock (Hirose et al, 2011;Telling et al, 2015), and the reduction of organic matter by microorganisms (Shuai, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Chinese basins, such as the Songliao (Guo Qingwu, 2004) and Bohai Bay (Meng Qingqiang, 2011) Basins in eastern China, the Sichuan (Zhang Shuichang et al, 2007;Xiao Zhihua et al, 2008) and Ordos (Liu et al, 2009) Basins in central-western China, and the Tengchong Basin (Shangguan Zhiguan and Huo Weiguo, 2002) in the southern China, all contain H 2 (Table 1). Usually, the H 2 concentration is low and varies in a large range from 0.01% (Meng Qingqiang, 2011;Meng Qingqiang et al, 2015) to 5.2% (Shangguan Zhiguan and Huo Weiguo, 2002).…”
Section: Hmentioning
confidence: 99%
“…Natural gas is generally dominated by gaseous alkanes with relatively simple chemical compositions compared to crude oil. The geochemical characteristics of natural gas, such as chemical composition, carbon and hydrogen isotopic composition, as well as noble gas isotopic composition are fundamental for the study of the origin, migration, accumulation and alteration of natural gas, and have played an important role in revealing the organic type, thermal evolution degree and sedimentary environment of natural gas source rocks (Stahl, 1977;Schoell, 1980;Chung et al, 1988;Prinzhofer and Huc, 1995;Rooney et al, 1995;Whiticar, 1999;Tang et al, 2000;Zhang Xiaobao et al, 2003;Dai et al, 2004;Zhu Guangyou et al, 2007;Liu Quanyou et al, 2011;Ni et al, 2011;Liu et al, 2014a;Meng et al, 2015;Tao Cheng et al, 2015;Fu Xiaofei et al, 2016;Liu et al, 2016;Ma Yongsheng and Zhao Peirong, 2016).…”
Section: Introductionmentioning
confidence: 99%